Prognostic Significance of Peripheral T‐Cell Subsets in Laryngeal Squamous Cell Carcinoma. Issue 5 (28th August 2019) - Marchi, Filippo; Missale, Francesco; Incandela, Fabiola; Filauro, Marta; Mazzola, Francesco; Mora, Francesco; Paderno, Alberto; Parrinello, Giampiero; Piazza, Cesare; Peretti, Giorgio
Abstract : Objectives: The role of the immune system in head and neck squamous cell carcinoma is controversial. The aim of our study was to analyze full blood counts and distribution of T cell subsets in patients affected by laryngeal squamous cell cancer (LSCC) and their association with clinical variables and survival. Study design: Retrospective study. Methods: We analyzed the levels of platelets, lymphocytes, and neutrophils, as well as the CD4 +, CD8 +, and CD3 + T‐cell subpopulations by cytofluorometry in LSCC patients. A cohort of healthy patients was used as control group. The disease‐specific survival (DSS) was considered as survival outcome. Results: Sixty‐five LSCC patients and 48 controls were enrolled. In LSCC patients, neutrophils were higher than in the healthy group ( P  < .0001). The neutrophil‐to‐lymphocyte ratio (NLR) and the platelet‐to‐lymphocyte ratio (PLR) were both higher in LSCC patients ( P  < .0001). In patients treated for recurrent disease, the CD8 + /CD3 + ratio was increased ( P = .02), while the CD4 + /CD8 + ( P = .03) and CD4 + /CD3 + ( P = .04) ratios were lower. In patients with lymph node metastases, leukocytes ( P = .03), CD3 + ( P = .04), and CD4 + ( P = .0098) were all higher. Among Stages III‐IV patients, low lymphocyte and low leukocyte count were associated with worse DSS. Conclusion: Our data demonstrate that NLR and PLR are significantly increased in LSCC. Lower CD4 + /CD8 + and CD3 + /CD8 + ratios are related to recurrent disease and a higher level of CD3 + and CD4 + is associated with nodal metastasis. Level of Evidence: 4